Implikasi Pernikahan Beda Agama Dalam Fiqh Islam Terhadap Kewargangaraan Dan Identitas Anak - Latifah Hannum Gultom; Johana Andriani Nainggolan; Agung Torang Sitohang; Syuratty Manalu (Al Fuadiy Jurnal Hukum Keluarga Islam, 2023)
Interfaith marriage has become a topic that has received great attention in the context of Islamic law. The implications of interfaith marriages in Islamic jurisprudence significantly influence the citizenship and identity of children. This article investigates the legal aspects related to interfaith marriages from the perspective of Islamic fiqh. At the legal level, interfaith marriages can raise questions about the rights and obligations of husband and wife, the legal status of marriage, and inheritance rights. Moreover, the implications for the child's citizenship and identity are important aspects to consider. This includes issues regarding determining a child's religious status, custody rights, national identity, and inheritance rights within the framework of Islamic law. By using the method applied in this article using a literature approach. Literature study is defined as a series of activities related to collecting data from library sources, reading, taking notes and processing research materials. This article also highlights the views of ulama as well as contemporary perspectives regarding legal solutions to problems arising from interfaith marriages, and how Islamic law addresses issues related to citizenship and identity of children in this context. Thus, this article aims to provide a deeper understanding of the legal implications of interfaith marriages in Islamic jurisprudence on the citizenship and identity of children.